Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Trace element sources, migration and health risks associated with river-groundwater interaction: Insights from isotopes, fluorescence spectroscopy and Monte Carlo simulation - Xu Yang; Muhan Li; Yiying Miao; Fuyang Huang; Zeyuan Liu; Hongli Ma; Ping Miao; Jigang Shi; Zengbao Zhang; Shen Qu; Ruihong Yu (Journal of Hydrology, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Information flow reveals three-tiered oceanic drivers of precipitation over the middle–lower Yangtze River Basin - Li-Ying Ning; Dan Wu; Ying Qu; Guo-Lin Feng; Yong-Ping Wu (Climate Dynamics, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Irrigation enhanced nitrification and hydrological partitioning drive groundwater nitrate accumulation in an agricultural irrigation district - Xu Yang; Ruihong Yu; Guanglei Yu; Yansong Bai; Shen Qu; Dong Qian; Muhan Li; Zeyuan Liu; Ping Miao; Hongli Ma (Journal of Hydrology, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Groundwater-surface water interactions and material fluxes in a typical watershed, Ordos Plateau, NW China: insight from hydrochemistry, stable isotopes and 222Rn mass balance model - Wei Bao; Yixuan Wang; Ao Gao; Jiping Yao; Shen Qu; Jiajun Li; Dong Qian; Le Qiao; Lijuan Hu; Hongli Ma; Ping Miao; Haixia Wu; et al. (Environmental Geochemistry and Health, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Splicing factor SC35 inhibits Nosema bombycis proliferation by regulating the alternative splicing of Bmupp1 - Qiong Yu; Qingsheng Qu; Shiyi Lu; Pingyang Wang; Li Sui; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

Functional characterization of fungal laccases via siRNA silencing enables targeted biodegradation - Jiaqi Sun; Lianyan Yuan; Mengna Niu; Ping Xu; Jinsheng Lin; Cuixin Li; Lin Ma; Huiping Li; Qiang Wang; Shaoxuan Qu (Environmental Pollution, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Research on anomaly detection and correction method for remote sensing instrument calibration data based on TELSTM-ADC model - Jianhua Qu; Ping Qin; Ling Sun; Weichu Yu; Shengli Wu; Qing Wang; Dongqi Li (International Journal of Remote Sensing, 2026)

In-situ construction of multi-site Co/Co-N-O porous carbons for plasma-catalytic toluene degradation - Chao Cao; Yixin Yang; Guangfei Qu; Rui Xu; Chenyang Zhao; Ping Ning; Junyan Li (Journal of Environmental Chemical Engineering, 2026)

Flash-spun composite fiber membranes for broadband electromagnetic absorption and multifunctionality - Daixuan Gong; Xincheng Wang; Meijie Qu; Shuhui Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2026)

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

FeC particle electrodes derived from copper slag boost peroxymonosulfate activation for efficient antibiotic degradation: non-radical pathways mediated by 3d orbital electron reconstruction - Linjin Li; Yaoze Wang; Guangfei Qu; Rui Xu; Yingying Cai; Minhua Cheng; Nanqi Ren; Ping Lu; Minjie He; Jun Wang (Bioresource Technology, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Synergistic effects of FeCl₃-derived deoxygenation and pore formation on TiFe hydrogen storage alloys - He Zhang; Yong Liu; Guodong Miao; Zhihui Ma; Feng Sun; Aimin Ju; Xuanhui Qu; Ping Li (Chemical Engineering Journal, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

Chlorchinaldol: A promising antiviral agent against iridoviruses in fish - Jia-Cheng Qin; Xiao-Ping Tan; Ying-Jie Jin; Guang-Shuo Wang; Shen-Ye Qu; Peng-Fei Li; Gao-Xue Wang; Fei Ling (Aquaculture, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Bimetallic cobalt-cerium loaded copper foam for enhanced paraxylene low-temperature catalytic oxidation: Mechanistic insights and role of oxygen vacancies - Chenyang Zhao; Huanhuan Wu; Guangfei Qu; Yongheng Yuan; Zheng Yuan; Guojun Liu; Zhishuncheng Li; Junyan Li; Yingying Cai; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Design and performance of moisture-responsive piezoelectric nanogenerators based on electrospinning poly(vinylidene fluoride) films - Shuhui Li; Meijie Qu; Yonghao Chen; Ping Tang; Xiaobin Liang; Ken Nakajima; Yuezhen Bin (Chemical Engineering Journal, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

A sensitive humidity-responsive actuator based on dispersing graphene oxide into chitosan- sodium alginate nanofibers - Yonghao Chen; Meijie Qu; Chenshen Liu; Shuhui Li; Xincheng Wang; Daixuan Gong; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Fe-doped TiO2 nanosheet exposure accelerates the spread of antibiotic resistance genes by promoting plasmid-mediated conjugative transfer - Ping Cheng; Botao Wang; Qianyu Ji; Pingping Yuan; Shixin Gui; Shuying Liang; Lin Li; Hongwei Xu; Shaoqi Qu (Journal of Hazardous Materials, 2025)

Advanced materials for CO2 capture and storage: A comprehensive review of current progress and future prospects - Jun Wang; Linjin Li; Guangfei Qu; Minhua Cheng; Yuanchuan Ren; Ping Lu; Ting Zhang; Yaoze Wang; Fenghui Wu (Journal of Environmental Chemical Engineering, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

The three-dimensional electrocatalytic oxidation system for refractory organic wastewater remediations: Mechanisms, electrode material and applications - Linjin Li; Yaoze Wang; Guangfei Qu; Ping Lu; Ting Zhang; Jun Wang; Minhua Cheng; Nanqi Ren; Yuanchuan Ren (Journal of Environmental Chemical Engineering, 2025)

Low-frequency rTMS Plays a Neuroprotective role in Pilocarpine-induced Status Epilepticus Rat Models Through the AMPAR GluA1–STIM–Ca2+ Pathway - Li-Qin Che; Zhen-Zhen Qu; Zhuo-Feng Mao; Qi Qiao; Kai-Ping Zhou; Li-Jing Jia; Wei-Ping Wang (Molecular Neurobiology, 2025)

Hydrochemical insights into spatiotemporal characteristics of groundwater salinization and health risk assessment of fluoride in the south bank of Yellow River irrigation area, Northwest China - Muhan Li; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Rina Wu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Environmental Geochemistry and Health, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Underlying the early signaling and gene expression of Pleurotus ostreatus mycelia during injury response - Jiachun Zhu; Jiaqi Sun; Huiping Li; Ping Xu; Lin Ma; Qiang Wang; Keping Chen; Shaoxuan Qu (World Journal of Microbiology and Biotechnology, 2025)

Study on the feasibility of buckwheat as a trap plant for flower thrips (Frankliniella intonsa) in sunflower field - Hui Qu; Jing Chang; Ze-Run Chuai; Wen-Bing Zhang; Jian Zhang; Jun Zhao; Hai-Ping Li (Journal of Pest Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Engineered bispecific antibodies with enhanced breadth and potency against SARS-CoV-2 variants and SARS-related coronaviruses - Fangfang Chang; Qian Wu; Yabin Hu; Zhendong Pan; Yong-Chen Liu; Yue-Zhou Li; Mihnea Bostina; Wenpei Liu; Ping Zhao; Xiaowang Qu; Yi-Ping Li (Medical Microbiology and Immunology, 2024)

Highly efficient removal and real-time visual detection of fluoride ions using ratiometric CAU-10-NH2@RhB: Probe design, sensing performance, and practical applications - Ping Ju; Wenhui Lu; Guixue Zhang; Shuping Wang; Anzhang Li; Qingxiang Zhang; Long Jiang; Ensheng Zhang; Fengli Qu (Journal of Hazardous Materials, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Renewable hemicellulose-based materials for value-added applications - Guangfu Liao; Enhui Sun; E.B. Gueguim Kana; Hongying Huang; Isaac A. Sanusi; Ping Qu; Hongmei Jin; Jun Liu; Li Shuai (Carbohydrate Polymers, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

SLCOBNet: Shrimp larvae counting network with overlapping splitting and Bayesian-DM-count loss - Yang Qu; Sheng Jiang; Daoliang Li; Ping Zhong; Zhencai Shen (Biosystems Engineering, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Evaluation and projection of circulation conditions tied to summertime compound drought and heatwave frequency over the Yangtze River Delta, China, for the carbon neutrality period based on CMIP6 GCMs - Jing Wang; Ping Liang; Fei Cheng; Yanju Liu; Chengyu Song; Wei Wu; Qingfeng Zheng; Tianyu Zhang; Ping Qu; Yujie Li; Yihui Ding (International Journal of Climatology, 2024)
Frequent occurrences of compound droughts and heatwaves (CDHWs) may have considerable adverse impacts on human health and socioeconomic development. To project future summertime CDHWs over the Yangtze River Delta (YRD) of China under carbon neutrality (CN) for policymakers, we used nine global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) and evaluated and projected circulation conditions tied to the summer YRD CDHW frequency in the boreal summer. The results show that a marked mid‐tropospheric regional‐scale anticyclonic anomaly centred over the East China Sea can be deemed the dominant system linking the more frequent occurrence of YRD CDHWs. Our selected nine CMIP6 GCMs better captured the observed climatological and anomalous spatial circulation patterns connected to the summer YRD CDHW frequency. Moreover, the nine models' multi‐model ensemble mean (9MME) was better than most of the individual models regarding the related climatological circulation simulations. The 9MME‐projected changes in circulation conditions tied to summer YRD CDHWs during the carbon neutrality period (2050–2060) under SSP119 favour the comparable occurrence of the YRD with that for the same period under the medium greenhouse gas (GHG) warming scenario (SSP245), but the intensities of the CDHWs are the least severe. However, the highest number of YRD CDHWs is driven by the high GHG warming scenario (SSP585), and these CDHWs feature the most severe intensity. Our research identified a new paradigm regarding the frequency and intensity of the summer YRD CDHW under SSP119, highlighting the potential role of the newly accessible CN‐oriented sustainable development pathway in alleviating compound extremes.

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Exploring the antiviral potential of paeonol from medicinal plants: A promising strategy for controlling white spot syndrome virus - Cheng Chen; Chang-Shuai Liang; Xiang-Yu Qu; Peng-Fei Li; Xiao-Ping Tan; Fei Ling; Gao-Xue Wang (Aquaculture, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Urea reduces the sustainability of soil Cd immobilization by upregulating the expression of AmSTOP1 and AmMATE genes in edible amaranth roots - Fo-Peng Wang; Jun-Feng Wang; Tao He; Ping Tian; Xiao-Qian Song; Qu-Sheng Li (Environmental Pollution, 2024)

Correlation of Gut Microbiota with Children Obesity and Weight Loss - Li-Jun Peng; Yan-Ping Chen; Fang Qu; Yan Zhong; Zhi-Sheng Jiang (Indian Journal of Microbiology, 2024)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Sodium alginate based energy harvesting fibers: Multiscale structure and moist-electrical properties - Rui Zhang; Hai Wang; Meijie Qu; Shuhui Li; Yue Ma; Xinye Li; Ping Tang; Yuezhen Bin (Chemical Engineering Journal, 2023)

Inoculation of Escherichia coli enriched the key functional bacteria that intensified cadmium accumulation by halophyte Suaeda salsa in saline soils - Tao He; Zhi-Min Xu; Jun-Feng Wang; Ke Zhang; Fo-Peng Wang; Wan-Li Li; Ping Tian; Qu-Sheng Li (Journal of Hazardous Materials, 2023)

Self-checking dual-modal aptasensor based on hybrid Z-scheme heterostructure of Zn-defective CdS/ZnS for oxytetracycline detection - Pei Song; Ping Qu; Min Wang; Ai-Jun Wang; Yadong Xue; Li-Ping Mei; Jiu-Ju Feng (Analytica Chimica Acta, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Highly efficient nitrobenzene removal by coupling electrochemical filtration with a microbial electrolysis cell - Jingjing Guo; Kuiling Li; Zhiyong Wang; Dan Qu; Ping Dang; Jun Wang (Journal of Environmental Chemical Engineering, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Single-base resolution mapping of 2′-O-methylation sites by an exoribonuclease-enriched chemical method - Ping Zhang; Junhong Huang; Wujian Zheng; Lifan Chen; Shurong Liu; Anrui Liu; Jiayi Ye; Jie Zhou; Zhirong Chen; Qiaojuan Huang; Shun Liu; Keren Zhou; et al. (Science China Life Sciences, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Deciphering the microbial community tolerance mechanism and alteration of antibiotic resistance genes during chloramphenicol wastewater treatment - Jia Zhou; Yan Chen; Wan-Xia Li; Jian-Hang Qu; Tian Chen; Yi-Ping Wang; Ning-Yu Geng (International Biodeterioration & Biodegradation, 2023)

Gas-in-place and its influence factors of the upper Paleozoic coal-bearing shale in the Qinshui Basin, China - Chengang Lu; Ping Gao; Gang Li; Yue Feng; Xiaorong Qu; Yufei Su; Xianming Xiao (Frontiers of Earth Science, 2023)

Contrasting relationships between plant-soil microbial diversity are driven by geographic and experimental precipitation changes - Xiaoan Zuo; Shanshan Sun; Shaokun Wang; Ping Yue; Ya Hu; Shengnlong Zhao; Xinxin Guo; Xiangyun Li; Min Chen; Xujun Ma; Hao Qu; Weigang Hu; et al. (Science of The Total Environment, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Degradation mechanism of HCN by electrochemically coupled copper-loaded magnetic nanoparticles in a liquid phase pseudo-homogeneous system - Guangfei Qu; Wei Ji; Junyan Li; Shuaiyu Liang; Zhishuncheng Li; Huimin Tang; Junhong Zhou; Ping Ning (Environmental Science and Pollution Research, 2022)

Probabilistic prediction of the spatial distribution of potential key blocks during tunnel surrounding rock excavation - Peng He; Li-ping Li; Gang Wang; Fei Xu; Shang-qu Sun (Natural Hazards, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Integration of metabolomics and transcriptomics revealed the biosynthetic mechanism of anti-parasitic compounds in Salinivibrio proteolyticus strain YCSC6 - Guangxun Du; Lingyun Qu; Ping Gao; Wenhao Huang; Chenghua Li; Dewen Ding (Journal of Oceanology and Limnology, 2022)

Responses of ecosystem respiration, methane uptake and nitrous oxide emission to drought in a temperate desert steppe - Ping Yue; Xiaoan Zuo; Kaihui Li; Xiangyun Li; Shaokun Wang; Xujun Ma; Hao Qu; Min Chen; Liangxu Liu; Tom Misselbrook; Qiang Yu (Plant and Soil, 2021)

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Functional analysis of indole 3-hexanoic acid as a novel auxin from Arabidopsis thaliana - Ping Song; Hui Xu; Jixiu Zhang; Huatao Chen; Li Li; Yana Qu; Feng Lin; Qun Zhang (Planta, 2021)

Aberrant activity within auditory network is associated with psychiatric comorbidities in interictal migraineurs without aura - Heng-Le Wei; Yu-Chen Chen; Yu-Sheng Yu; Xi Guo; Gang-Ping Zhou; Qing-Qing Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress - Huirong Lv; Yanli Liu; Haidong Li; Xiaolong Yin; Ping Wang; Xiaoyu Qu; Yang Gao; Weiye Li; Zhangjie Chu (Frontiers in Marine Science, 2021)
The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for 3 days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8 from 12°C; T2 represents the group that sampled when the fish had been kept at 8°C for 3 days; T3 represents the group sampled when the water temperature was increased to 12 from 8°C. The antioxidant abilities of the liver, muscle, and intestine of large yellow croaker at different temperatures and times were determined, and the expression of HSP70 and HSP90 in the liver as well as the changes in intestinal microbiota were investigated. The results showed that the activities of SOD, CAT, GSH-Px, and MDA content increased significantly when the water temperature decreased from 12 to 8°C, significantly higher than those in the control group. The gene expression levels of HSP70 and HSP90 in the liver of large yellow croaker significantly increased under low temperature stress and were significantly higher than those in the control group. The diversity and abundance of intestinal microbiota of large yellow croaker were altered when the water temperature was maintained at 8°C, although the change was not obvious. Proteobacteria, Firmicutes, and Bacteroidetes were the dominate phyla in both the 12 and 8°C groups, and the temperature variation did not change the functional pathways of the microbiota. In conclusion, the acute temperature variation affected the antioxidant ability and heat shock protein expression of large yellow croaker but did not affect the diversity or abundance of the intestinal microbiota. These results will provide a theoretical basis for studying the mechanisms of large yellow croaker overwintering and adaptation to low temperatures.

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Comparison of Long-Term Outcomes of Endoscopic and Minimally Invasive Catheter Evacuation for the Treatment of Spontaneous Cerebellar Hemorrhage - Leiyang Li; Haixiao Liu; Jianing Luo; Zhijun Tan; Junmei Gao; Ping Wang; Wenting Jing; Ruixi Fan; Xiaoyang Zhang; Hao Guo; Hao Bai; Wenxing Cui; et al. (Translational Stroke Research, 2021)
Recently, minimally invasive techniques, including endoscopic evacuation and minimally invasive catheter (MIC) evacuation, have been used for the treatment of patients with spontaneous cerebellar hemorrhage (SCH). However, credible evidence is still needed to validate the effects of these techniques. To explore the long-term outcomes of both surgical techniques in the treatment of SCH. Fifty-two patients with SCH who received endoscopic evacuation or MIC evacuation were retrospectively reviewed. Six-month mortality and the modified Rankin Scale (mRS) score were the primary and secondary outcomes, respectively. A multivariate logistic regression model was used to assess the effects of the different surgical techniques on patient outcomes. In the present study, the mortality rate for the entire cohort was 34.6%. Univariate analysis showed that the surgical technique and preoperative Glasgow Coma Scale (GCS) score affected 6-month mortality. However, no variables were found to be correlated with 6-month mRS scores. Further multivariate analysis demonstrated that 6-month mortality in the endoscopic evacuation group was significantly lower than that in the MIC evacuation group (OR = 4.346, 95% CI 1.056 to 17.886). The 6-month mortality rate in the preoperative GCS 9–14 group was significantly lower than that in the GCS 3–8 group (OR = 7.328, 95% CI 1.723 to 31.170). Compared with MIC evacuation, endoscopic evacuation significantly decreased 6-month mortality in SCH patients. These preliminary results warrant further large, prospective, randomized studies.

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Impaired functional connectivity of limbic system in migraine without aura - Heng-Le Wei; Jinan Chen; Yu-Chen Chen; Yu-Sheng Yu; Gang-Ping Zhou; Li-Jie Qu; Xindao Yin; Junrong Li; Hong Zhang (Brain Imaging and Behavior, 2020)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Serratia microhaemolytica sp. nov., isolated from an artificial lake in Southern China - Juan Wang; Min-Ling Zheng; Jian-Yu Jiao; Wei-Jia Wang; Shuai Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Digitizing and modeling of structural planes in fractured rock mass tunnel based on SfM - Shang-qu Sun; Li-ping Li; Cheng-shuai Qin; Hong-liang Liu; Yan-huan Zhang; Xing-zhi Ba (Arabian Journal of Geosciences, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Inhibition of thymocyte autophagy-associated CD4+T thymopoiesis is involved in asthma susceptibility in mice exposed to caffeine prenatally - Han-xiao Liu; Hui-yi Yan; Wen Qu; Xiao Wen; Li-fang Hou; Wen-hao Zhao; Jie Ping (Archives of Toxicology, 2019)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Low-thermal remediation of mercury-contaminated soil and cultivation of treated soil - Ting Zhao; Zhi Yu; Junfang Zhang; Liya Qu; Ping Li (Environmental Science and Pollution Research, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Rockfall Hazard Assessment on Wangxia Rock Mass in Wushan (Chongqing, China) - Shang-qu Sun; Li-ping Li; Shu-cai Li; Qian-qing Zhang; Cong Hu (Geotechnical and Geological Engineering, 2017)

Analysis of Dynamic Fracture Compliance Based on Poroelastic Theory. Part I: Model Formulation and Analytical Expressions - Ding Wang; Shou-Li Qu; Ping-Bo Ding; Qun Zhao (Pure and Applied Geophysics, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Prismatic and full-waveform joint inversion - Ying-Ming Qu; Zhen-Chun Li; Jian-Ping Huang; Jin-Li Li (Applied Geophysics, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Two phthalide dimers from the radix of Angelica sinensis - Xing-Nuo Li; Yuan-Yi Chen; Dong-Ping Cheng; Sheng-Qiang Tong; Hai-Bin Qu; Ji-Zhong Yan (Natural Product Research, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

The distribution and expression of claudin-5 and occludin at the rat blood–optic nerve barrier after borneol treatment - Di Jin; Feng Wang; Lijun Qu; Zhituo Li; Lianhong Jin; Ping Liu; Xiaolin Xu; Hao Cui (Molecular Biology Reports, 2011)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Two novel cSNPs of weaver gene in Chinese indigenous goat and their associations with milk yield - Zhuanjian Li; Zhongqi Chen; Xianyong Lan; Liang Ma; Yujiao Qu; Yanli Liu; Mijie Li; Ping Wang; Fei Li; Hong Chen (Molecular Biology Reports, 2010)

Localization of QTL for basal root thickness in japonica rice and effect of marker-assisted selection for a major QTL - Lifeng Liu; Ping Mu; Xueqin Li; Yanying Qu; Yi Wang; Zichao Li (Euphytica, 2008)

Mapping QTLs of root morphological traits at different growth stages in rice - Yanying Qu; Ping Mu; Hongliang Zhang; Charles Y. Chen; Yongming Gao; Yuxiu Tian; Feng Wen; Zichao Li (Genetica, 2008)

Biodecolorization of Azo Dye Acid Red B under High Salinity Condition - M. Salah Uddin; Jiti Zhou; Yuanyuan Qu; Jianbo Guo; Ping Wang; Li hong Zhao (Bulletin of Environmental Contamination and Toxicology, 2007)